Extending lean manufacturing in supply chains: a successful case in Brazil - Omodei Júnior, José Carlos; Jabbour, Ana Beatriz Lopes de Sousa; Jabbour, Charbel José Chiappetta [UNESP] (My University, 2014)
Purpose – The purpose of this paper is to present the results of a success story involving the extending of lean manufacturing practices between a focal firm and its supplier, both located in Brazil, thereby configuring a case of excellence. Design/methodology/approach – An in-depth case study was conducted involving two companies: Company A, focal, leader in its segment, located in Brazil; and Company B, Company A's supplier, also located in Brazil. Findings – Results indicate there are several mechanisms for extending lean manufacturing practices in the supply chain, such as workshops, training, and integrated teams. These mechanisms are shown and guidelines are also introduced for companies seeking to successfully extend lean manufacturing practices. Originality/value – An original use of define, measure, analyze, improve, control for structuring the extending of lean manufacturing practices to suppliers and, consequently, the importance of the lean six-sigma relationship in this context. Furthermore, the guidelines introduced serve as a benchmark for other companies interested in the topic.
Keywords: Supply chain; Brazil; DMAIC; Dissemination; Benchmarking; Lean manufacturing; Lean production; Extending